Hellenistic Alexandria : celebrating 24 centuries - Zerefos, C. S; Bardinogiannē, Marianna B. (2019)
This proceedings volume includes high-level dialogues and philosophical discussions between international experts on Hellenistic Alexandria. The goal was to celebrate the 24 centuries which have elapsed since its foundation and the beginning of the Library and the Museum of Alexandria.